Možnosti využití benchmarkingu v českém zdravotnictví - Kalašová, Irena (Univerzita Pardubice, 2006)
Cílem této diplomové práce je ověřit, zda je možné využít benchmarking v oblasti veřejného sektoru, a to konkrétně ve zdravotnictví, a ukázat aplikaci benchmarkingu na vzorku českých nemocnic. Tato práce je rozdělena na čtyři části, kde jsou popsány podstata benchmarkingu, specifika zdravotnictví a ukazatele, které budou u jednotlivých nemocnic sledovány. Poslední část je zaměřena na aplikaci benchmarkingu na vybraný vzorek českých nemocnic.

The aim of this thesis is verified, whether is possibly applied a benchmarking in the public sector, concrete in the Health Service, and showed the applications of the benchmarking on the sample of the Czech hospitals. This work is devided into four main parts, where are described the substance of the benchmarking, the specifications of the Health Service and the indices, which will be watching by the single hospitals. The last main part is intented on the application of the benchmarking on the choice sample of the Czech hospitals.
Facilities of applying a benchmarking in the czech health service
Keywords: Heatlh Service; Financial analysis; profibilities; liquidities; benchmarking; Zdravotnictví; finanční analýzy; rentabilita; likvidita